The limits of legitimate business interest with respect to processing of children's data - Šuta, Marija (Riga Graduate School of Law, 2019)
The research is specifically focused on processing of children's data since it is an even more focused field of data protection which is given separate provisions in international and national legislation. Moreover, it is relatively less considered group of people when examining data protection prerequisites. In order to ensure data protection, being defined as fundamental human right, there should be legal data processing. Therefore, the focus of this research is on basis of the processing of children’s data for information society services provision and online marketing purposes being the most frequent aims used for child data processing.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Commercial and company law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::International private law and international procedural law; Children rights; Data protection